Testing and Evaluation of Preference Marketplace Web Application - Isaev, Samet; Moreno, Mariale; Makatsoris, Harris (Cranfield University, 2017)
Preference marketplace is digital crowdsourcing tool which employs game mechanics to engage consumers in order to understand their requirements and prioritise the most required product attributes and concepts. A number of case study including food and beverage products has been employed to test the performance of the platform. This platform is web application under development by the Harris Makatsoris research group. Workshops were organised by theHarris Makatsoris research group to collect data at Cranfield University.
Keywords: 'Digital crowdsourcing'; 'preference marketplace'; 'gamification'; 'new oodporuct development'; 'Flexible Manufacturing Systems'; 'Food Processing'; 'Consumer-Oriented Product or Service Development'